Deflation and Depression: Is There an Empirical Link? - Atkeson, Andrew; Kehoe, Patrick J (American Economic Review, 2004)
Are deflation and depression empirically linked? No, concludes a broad historical study of inflation and real output growth rates. Deflation and depression do seem to have been linked during the 1930s. But in the rest of the data for 17 countries and more than 100 years, there is virtually no evidence of such a link.